English as the language of international communication - Fair, V.; Mikhalchuk, O. M.; Феєр, В.; Михальчук, O. M. (Вінницька міська друкарня, 2020)
The purpose of this article is to investigate English as a language of international communication and to analyze the causes and consequences of its global spread.
Англійська як мова міжнародного спілкування
Keywords: English; international communication